Pengaruh Permainan Papan Perkenalan Terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun di TK X Kabupaten Bandung - Shela Isna Noviadana (Jurnal Riset Pendidikan Guru Paud, 2021)
Abstract. The purpose of this study was to determine the effect of introductory board games on the speaking skill for 5-6 years old in X Kindergarten, Bandung Regency. This study uses a quantitative method with quasi-experimental design and nonequivalent control group design. The sampling method is probability sampling with cluster random sampling technique. The sample of this research is B2-class as an experimental class and B3-class as a control class. Both classes consist of 10 students. Data collection techniques by using observation sheets and documentation. In this study, the instrument prerequisite test is used to test the validity and reliability. The data analysis technique is the normality test using Shapiro Wilk, the homogeneity test using the Levene statistic test, and hypothesis testing using the Paired Sample t-test. The results of hypothesis testing concluded that the value of sig. (2-tailed) = 0.020, it is smaller than 0.05. So that it is accepted and H0 is rejected with an average value of 63.90 in the experimental class and an average value of 53.30 in the control class. It can be concluded that there is a significant influence of the introductory board game on the speaking skills for 5-6 years olds in Asy Syamsi Kindergarten, Bandung Regency. The ability to speak with introductory board games in the experimental class increases scores 10,6 than the control class. So it can be said that the introductory board game has an influence on the speaking skills for 5-6 years olds in X Kindergarten, Bandung Regency. Abstrak. Penelitian ini memiliki tujuan mengetahui pengaruh permainan papan perkenalan terhadap kemampuan berbicara anak usia 5-6 tahun di TK X Kabupaten Bandung. Penelitian ini menggunakan pendekatan kuantitatif quasi eksperimental design dengan bentuk nonequivalent control grup design. Teknik pengambilan sampel menggunakan probablility sampling dengan cluster random sampling. Sampel ialah kelas eksperimen (B2) dan kelas kontrol (B3) ssetiap kelas terdiri dari 10 anak didik. Teknik pengumpulan data dengan observasi dan dokumentasi. Teknik analisis data dengan uji normalitas menggunakan Shapiro wilk, uji homogenitas menggunakan uji levene statistik, dan uji hipotesis menggunakan Paired Sample t-test. Hasil pengujian hipotesis disimpulkan bahwa nilai sig. (2-tailed) = 0,020 lebih kecil dari α 0,05, maka Ha di terima dan H0 di tolak dengan mean kelas eksperimen 63,90 dan mean kelas kontrol 53,30 sehingga disimpulkan bahwa terdapat pengaruh signifikan permainan papan perkenalan terhadap kemampuan berbicara anak usia 5 – 6 tahun di TK Asy Syamsi Kabupaten Bandung. Kemampuan berbicara dengan permainan papan perkenalan pada kelas eksperimen meningkatkan nilai yang lebih tinggi 10,6 dibanding kelas kontrol. Sehingga dikatakan bahwa permainan papan perkenalan berpengaruh terhadap kemampuan berbicara anak usia 5 – 6 tahun di TK X Kabupaten Bandung.